Development of a Novel Wearable Posture Correction Apparatus Using Advanced Accelerometry Techniques: Signal Analysis Unit - Zha, Nanxi (My University, 2010)
Proper posture is an integral part of a healthy lifestyle. For individuals suffering from unilateral body neglect, proper posture cannot always be guaranteed. The wearable posture correction apparatus uses measurements from accelerometers. Based on gravitational acceleration, calculations are performed to measure posture tilt. This action is modeled on a software program. Improper posture is also noted, and corrective instructions are given. The theory behind our device, hardware design, the experimental results, and correctness of the system are presented.
Keywords: Posture correction; accelerometer; tilt; unilateral body neglect; Biomedical; Electrical and Computer Engineering; Biomedical